Modified sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof
By using sol-gel method and rare earth metal element doping method in sodium ion battery positive electrode material, a three-dimensional network frame structure is formed, which solves the problems of poor processability and cycle stability of polyanionic positive electrode material, and achieves efficient cycle stability and capacity retention of sodium ion battery.
Patent Information
- Application Number
- CN202510055758.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyanionic cathode materials of sodium ion batteries have problems such as poor processability, unfavorable phase change in electrochemical reactions, phase structure transformation and volume change during charging and discharging, resulting in poor cycle stability.
The rare earth metal-doped pyrophosphate polyanionic compound was prepared by sol-gel method and doping by rare earth metal elements to form a three-dimensional network framework structure with three oblique phases to inhibit adverse phase transformation and phase structure transformation.
The electrochemical cycling stability of the positive electrode material of sodium ion battery is improved, the sodium ion diffusion coefficient is enhanced, and the interfacial charge transfer impedance is reduced, and the capacity retention rate reaches up to 94% after cycling for 1600 cycles at a 10C current density.
Smart Images

Figure CN119852396A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium iron pyrophosphate positive electrode materials for sodium ion batteries, and in particular to a modified sodium iron pyrophosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] The successful commercial use of lithium-ion batteries has made people realize the efficiency and convenience of electrochemical energy storage methods. Its rapid development has successfully changed the way people live, learn and work. However, the non-renewable nature of lithium resources and the demand for lithium-ion batteries have caused the price of lithium-ion batteries to continue to rise. Therefore, it is urgent to explore new secondary battery systems with abundant resources, low cost and high energy density as an ideal supplement to lithium-ion batteries. As the fourth most abundant metal element in the earth's crust (about 2.83%), sodium has natural advantages such as reasonable distribution and easy extraction. It is also in the same main group as lithium and has similar properties. Therefore, sodium-ion batteries are the only choice to supplement lithium-ion batteries and have been widely studied.
[0003] The cathode materials of sodium ion batteries mainly include four types: oxides, polyanions, Prussian blue, and organic cathode materials. Among them, oxide and polyanion cathode materials have received extensive attention. Oxide cathode materials have a higher theoretical specific capacity and are suitable for the development of secondary batteries with high energy density, while polyanion cathode materials have a more stable structure and are suitable for the development of secondary batteries with long life. Among them, according to the different types of anions, polyanion cathode materials can be mainly divided into six categories: phosphates, pyrophosphates, sulfates, silicates, phosphoric acid / pyrophosphate mixed salts, fluorophosphate mixed salts, etc. Different from the problems of common polyanion cathode materials, such as the large proportion of high-cost V elements used in sodium vanadium phosphate cathode materials, or the F elements that are difficult to control for material preparation, iron-based phosphate or phosphoric acid / pyrophosphate mixed salt cathode materials have become one of the hot spots in the research of sodium ion battery cathode materials at home and abroad due to their convenient raw materials and high reversible specific capacity.
[0004] The sodium ion battery polyanion positive electrode material that was studied earlier is sodium iron phosphate (NaFePO4), which has good sodium storage performance. However, considering that this highly dispersed nanomaterial often has poor processability, for example, the tap density and the compaction density when preparing the electrode are relatively low, the practical prospects are poor. Compared with NaFePO4, the pyrophosphate positive electrode material sodium iron pyrophosphate (Na2FeP2O7) also has good electrochemical properties, a simple preparation process, and better thermal stability. It is a material with scientific research and application value. The phosphate group supports the three-dimensional structure of Na +The migration of ions provides a large number of pores, and the internal induction effect can increase the voltage platform of the battery, and the stability of the material is improved by the presence of PO bonds. However, its most obvious disadvantage is that its inherent theoretical capacity is not high. Therefore, the use of ion doping, a common electrode material optimization strategy, to modify the pyrophosphate positive electrode material can achieve a change in the intrinsic conductivity of the material.
[0005] Among them, rare earth elements (RE) are widely regarded as vitamins of modern industry, and are considered beneficial to LIB (lithium-ion battery) and SIB (sodium-ion battery) due to their excellent properties such as high conductivity, large ionic radius and high self-polarization ability. Sc-doped NASICON solid electrolytes exhibit excellent Na-ion conductivity and improved cycling performance, which is due to the expansion of the rhombohedral phase lattice volume and the change of Na-O bond length. In addition, lanthanum (La) and yttrium (Y) elements have higher bond energy and larger radius, and their addition can effectively expand the Na + Therefore, the use of rare earth metal elements to dope has a wide range of application prospects for improving the electrochemical performance of sodium iron pyrophosphate positive electrode materials. Summary of the invention
[0006] The purpose of the present invention is to provide a modified sodium iron pyrophosphate positive electrode material and a preparation method and application thereof, which adopts a sol-gel method and doping with rare earth metal elements to inhibit the adverse phase change of the polyanion positive electrode material of the sodium ion battery in the electrochemical reaction, the phase structure transformation and volume change in the charging and discharging process, and improve the electrochemical cycle stability.
[0007] To achieve the above object, the present invention provides a modified sodium iron pyrophosphate positive electrode material, which is a rare earth metal-doped pyrophosphate polyanion compound, and its structure is a triclinic three-dimensional network framework structure.
[0008] The present invention provides a method for preparing a modified sodium iron pyrophosphate positive electrode material, comprising the following steps:
[0009] Step 1, preparing precursor gel;
[0010] Step 2, preparing dried gel;
[0011] Step 3: Prepare positive electrode material powder.
[0012] Preferably, the specific operation of step one is: dissolving the sodium source, iron source, phosphate source, carbon source and rare earth metal source in deionized water, stirring until completely dissolved and presenting a transparent yellow-brown color, heating the solution while continuously stirring until a yellow-green gel is obtained.
[0013] Preferably, the specific operation of step 2 is: vacuum drying the yellow-green gel obtained in step 1 to obtain a dried gel.
[0014] Preferably, the specific operation of step three is: sintering the dried gel obtained in step two, and grinding the sintered product to obtain black powder, namely, positive electrode material powder.
[0015] Preferably, in step 1, the sodium source is one or more of sodium acetate, sodium carbonate, sodium bicarbonate and sodium nitrate, the iron source is one of ferric nitrate nonahydrate and ferric sulfate, the phosphate source is one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate, the carbon source is one or more of citric acid monohydrate, sucrose, ascorbic acid and glucose, and the rare earth metal source is one or more of scandium nitrate, yttrium nitrate, lanthanum nitrate, neodymium nitrate and praseodymium nitrate.
[0016] Preferably, in step 1, the molar ratio of the sodium source, iron source, phosphate source, carbon source and rare earth metal source is 2:1:2:1:0.01-0.05, the amount of deionized water is 20-50 mL, the heating temperature is 60-100° C., the heating time is 3h-6h, and the stirring time is 4h-8h.
[0017] Preferably, the vacuum drying in step 2 is carried out at 100-150° C. for 10-12 hours.
[0018] Preferably, in step three, the sintering temperature is 500-800° C., the heating rate is 3-5° C. / min, the sintering time is 10-12 h, and the protective gas during sintering is argon.
[0019] The present invention also provides an application of a sodium iron pyrophosphate positive electrode material, and the above-mentioned sodium iron pyrophosphate positive electrode material is applied to a sodium ion battery.
[0020] In order to solve the problem of low electronic conductivity of polyanion cathode materials, the present invention designs and prepares rare earth metal-doped Na2FeP2O7 / C composite cathode materials. Compared with undoped samples, the doped samples have higher sodium ion diffusion coefficients and lower interfacial charge transfer impedances, which inhibit the adverse phase changes of polyanion cathode materials in sodium ion batteries during electrochemical reactions, phase structure changes during charge and discharge, and volume changes, thereby improving electrochemical cycle stability.
[0021] Therefore, the present invention adopts the above-mentioned modified sodium iron pyrophosphate positive electrode material and its preparation method and application, which has the following beneficial effects:
[0022] (1) The sodium iron pyrophosphate positive electrode material of the present invention replaces Fe with rare earth metal elements and stabilizes the lattice through doping, thereby optimizing the cycle stability of the sodium ion battery.
[0023] (2) The sodium ion battery prepared using the sodium iron pyrophosphate positive electrode material prepared by the present invention has good cycle stability. After 1600 cycles at a current density of 10C, the capacity retention rate is as high as 94%.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a modified sodium iron pyrophosphate positive electrode material of the present invention, a preparation method thereof, and XRD patterns of Na2FeP2O7 (NFP@C) and Na2FeP2O7-Sc, Na2FeP2O7-Y, and Na2FeP2O7-La (NFP-Sc@C, NFP-Y@C, and NFP-La@C) materials obtained by using Comparative Example 1 and Examples 1-3;
[0026] Figure 2 It is a scanned image of a modified sodium iron pyrophosphate positive electrode material of the present invention and a preparation method thereof and an NFP@C material prepared by using comparative example 1;
[0027] Figure 3 It is a scanned image of a modified sodium iron pyrophosphate positive electrode material and a preparation method thereof and an NFP-Sc@C material obtained in Application Example 1 of the present invention;
[0028] Figure 4 It is a transmission image and element distribution image of a modified sodium iron pyrophosphate positive electrode material and a preparation method thereof and an NFP-Sc@C material obtained in Application Example 1 of the present invention;
[0029] Figure 5 It is a scanned image of a modified sodium iron pyrophosphate positive electrode material and a preparation method thereof and an NFP-Y@C material obtained in Application Example 2 of the present invention;
[0030] Figure 6 It is a scanned image of a modified sodium iron pyrophosphate positive electrode material and a preparation method thereof and an NFP-La@C material obtained in Example 3 of the present invention;
[0031] Figure 7 It is a cycle performance diagram of a modified sodium iron pyrophosphate positive electrode material of the present invention, a preparation method thereof, and button batteries assembled in application examples 1-3 under 10C conditions. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0034] The invention provides a modified sodium iron pyrophosphate positive electrode material. The modified sodium iron pyrophosphate positive electrode material is a rare earth metal-doped pyrophosphate polyanion compound, and the structure of the modified sodium iron pyrophosphate positive electrode material is a triclinic three-dimensional network framework structure.
[0035] The above-mentioned method for preparing a modified sodium iron pyrophosphate positive electrode material comprises the following steps:
[0036] Step 1: Prepare precursor gel: dissolve the sodium source, iron source, phosphate source, carbon source and rare earth metal source in deionized water, stir until completely dissolved and present a transparent yellow-brown color, heat the solution and continue stirring until a yellow-green gel is obtained.
[0037] Wherein, in step 1, the sodium source is one or more of sodium acetate, sodium carbonate, sodium bicarbonate and sodium nitrate, the iron source is one of ferric nitrate nonahydrate and ferric sulfate, the phosphate source is one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate, the carbon source is one or more of citric acid monohydrate, sucrose, ascorbic acid and glucose, and the rare earth metal source is one or more of scandium nitrate, yttrium nitrate, lanthanum nitrate, neodymium nitrate and praseodymium nitrate.
[0038] The molar ratio of the sodium source, the iron source, the phosphate source, the carbon source and the rare earth metal source is 2:1:2:1:0.01-0.05, the amount of deionized water is 20-50 mL, the heating temperature is 60-100° C., the heating time is 3 h-6 h, and the stirring time is 4 h-8 h.
[0039] Step 2, preparing a dried gel: vacuum drying the yellow-green gel obtained in step 1 to obtain a dried gel, wherein the vacuum drying is performed at 100-150° C. for 10-12 hours.
[0040] Step 3: preparing positive electrode material powder: sintering the dried gel obtained in step 2, and grinding the sintered product to obtain black powder, namely, positive electrode material powder.
[0041] The sintering temperature is 500-800°C, the heating rate is 3-5°C / min, the sintering time is 10-12h, and the protective gas during sintering is argon.
[0042] The sodium iron pyrophosphate positive electrode material described above is applied to sodium ion batteries.
[0043] Example 1
[0044] Preparation of rare earth metal element scandium (Sc) doped modified sodium iron pyrophosphate positive electrode material (Na2FeP2O7-Sc):
[0045] Dissolve ferric nitrate nonahydrate in 35 mL of deionized water, stir until completely dissolved and transparent yellow-brown, then add citric acid monohydrate, anhydrous sodium carbonate, ammonium dihydrogen phosphate, and scandium nitrate to deionized water in a molar ratio of 1:2:2:0.03. Heat the solution at 70 ° C for 5 hours and continue stirring for 5 hours until a yellow-green gel is obtained, and vacuum dry it at 100 ° C for 10 hours to obtain a dry gel. Sinter the obtained gel at a sintering temperature of 500 ° C, a heating rate of 3 ° C / min, a sintering time of 10 hours, and use argon protection. Grind the sintered product to obtain a black powder.
[0046] Example 2
[0047] Preparation of rare earth metal element yttrium (Y) doped modified sodium iron pyrophosphate positive electrode material (Na2FeP2O7-Y):
[0048] Dissolve ferric nitrate nonahydrate in 35 mL of deionized water, stir until completely dissolved and transparent yellow-brown, then add citric acid monohydrate, anhydrous sodium carbonate, ammonium dihydrogen phosphate, and yttrium nitrate to deionized water in sequence according to a molar ratio of 1:2:2:0.03. Heat the solution at 70 ° C for 5 hours while stirring for 5 hours until a yellow-green gel is obtained, and vacuum dry it at 500 ° C for 10 hours to obtain a dry gel. Sinter the obtained gel at a sintering temperature of 500 ° C, a heating rate of 3 ° C / min, a sintering time of 10 hours, and use argon protection. Grind the sintered product to obtain a black powder.
[0049] Example 3
[0050] Preparation of rare earth metal element lanthanum (La) doped modified sodium iron pyrophosphate positive electrode material (Na2FeP2O7-La):
[0051] Dissolve ferric nitrate nonahydrate in 35 mL of deionized water, stir until completely dissolved and transparent yellow-brown, then add citric acid monohydrate, anhydrous sodium carbonate, ammonium dihydrogen phosphate, and lanthanum nitrate to deionized water in a molar ratio of 1:2:2:0.03. Heat the solution at 70 ° C for 5 hours while stirring for 5 hours until a yellow-green gel is obtained, and vacuum dry it at 500 ° C for 10 hours to obtain a dry gel. Sinter the obtained gel at a sintering temperature of 500 ° C, a heating rate of 3 ° C / min, a sintering time of 10 hours, and use argon protection. Grind the sintered product to obtain a black powder.
[0052] Comparative Example 1
[0053] The only difference between Comparative Example 1 and Example 1 is that no scandium nitrate is added in Comparative Example 1, and other conditions are the same as those in Example 1.
[0054] Depend on Figure 1It can be seen that compared with Example 1, the XRD results of the synthesized Na2FeP2O7-Sc and Na2FeP2O7 are highly consistent, proving that the Na2FeP2O-Sc material is high-purity and free of impurities.
[0055] Compared with Example 1, the XRD results of the synthesized Na2FeP2O7-Y in Example 2 are highly consistent with those of Na2FeP2O7, proving that the Na2FeP2O7-Y material is high-purity and free of impurities.
[0056] Compared with Comparative Example 1, Example 3 shows that the XRD results of the synthesized Na2FeP2O7-La are highly consistent with those of Na2FeP2O7, proving that the Na2FeP2O7-La material is of high purity and free of impurities.
[0057] Depend on Figure 2 and Figure 3 By comparison, the morphology of the synthesized Na2FeP2O7-Sc particles is smaller and denser than that of Na2FeP2O7 particles. Figure 2 and Figure 5 By comparison, the synthesized Na2FeP2O7-Y particles are smaller and denser. Figure 2 and Figure 6 By comparison, the synthesized Na2FeP2O7-La particles are smaller and denser in morphology.
[0058] Figure 4 (a) and Figure 4 (b) is the transmission image of NFP-Sc@C at different magnifications, and Figure 4 (b) It can be seen that the synthesized Na2FeP2O7-Sc has an obvious carbon coating layer and lattice fringes, and the lattice spacing corresponds to the (1-11) crystal plane of the Na2FeP2O7 material. Figure 4 (c)-(i) in the figure are the transmission mapping images of NFP-Sc@C material. It can be clearly seen from the figure that the material contains C, Na, Fe, P, O, and Sc elements.
[0059] Performance Test:
[0060] The half-cells of Examples 1-3 were assembled in a glove box for testing to verify the effect of rare earth metal element doping on the electrochemical performance of Na2FeP2O7 cathode materials. The obtained Na2FeP2O7-Sc, Na2FeP2O7-Y, and Na2FeP2O7-La were used as cathodes, sodium metal sheets as anodes, and sodium perchlorate as electrolyte. The battery was assembled in an argon-protected glove box using a 2032 button cell. The results of the cycle number-specific capacity-coulomb efficiency curve under the current condition of 10C are shown in Figure 7 .
[0061] The Na2FeP2O7 electrode in Comparative Example 1 was used to assemble a half-cell. The assembly process was as follows: Na2FeP2O7 was used as the positive electrode, the metal sodium sheet was used as the negative electrode, the electrolyte was sodium perchlorate, and the battery was assembled in an argon-protected glove box using a 2032 button cell. The results of the cycle number-specific capacity-coulomb efficiency curve under the current condition of 10C can be found in Figure 7 .
[0062] Depend on Figure 7 It can be seen that under 10C conditions, the discharge specific capacities of Na2FeP2O7, Na2FeP2O7-Sc, Na2FeP2O7-Y, and Na2FeP2O7-La are 46 mA·hg -1 、74mA·hg -1 、63mA·hg -1 、61mA·hg -1 , and there is no obvious attenuation after 1600 cycles. This shows that the capacity of the Na2FeP2O7 cathode material modified by rare earth metal elements is significantly improved compared with the unmodified Na2FeP2O7 cathode material.
[0063] Therefore, the present invention adopts the above-mentioned modified sodium iron pyrophosphate positive electrode material and its preparation method and application, adopts the sol-gel method and doping with rare earth metal elements to inhibit the adverse phase change of the sodium ion battery polyanion positive electrode material in the electrochemical reaction, the phase structure transformation and volume change during the charge and discharge process, and improve the electrochemical cycle stability.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A modified sodium iron pyrophosphate positive electrode material, characterized in that: The modified sodium iron pyrophosphate positive electrode material is a rare earth metal-doped pyrophosphate polyanion compound, and its structure is a triclinic three-dimensional network framework structure.
2. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1, preparing precursor gel; Step 2, preparing dried gel; Step 3: Prepare positive electrode material powder.
3. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 2, characterized in that: The specific operation of step one is: dissolving the sodium source, iron source, phosphate source, carbon source and rare earth metal source in deionized water, stirring until they are completely dissolved and present a transparent yellow-brown color, and heating the solution while continuously stirring until a yellow-green gel is obtained.
4. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 2, characterized in that: The specific operation of step 2 is: vacuum drying the yellow-green gel obtained in step 1 to obtain a dried gel.
5. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 2, characterized in that: The specific operation of step three is: sintering the dried gel obtained in step two, and grinding the sintered product to obtain black powder, namely, positive electrode material powder.
6. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 3, characterized in that: In step 1, the sodium source is one or more of sodium acetate, sodium carbonate, sodium bicarbonate and sodium nitrate, the iron source is one of ferric nitrate nonahydrate and ferric sulfate, the phosphate source is one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate, the carbon source is one or more of citric acid monohydrate, sucrose, ascorbic acid and glucose, and the rare earth metal source is one or more of scandium nitrate, yttrium nitrate, lanthanum nitrate, neodymium nitrate and praseodymium nitrate.
7. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 3, characterized in that: In step 1, the molar ratio of the sodium source, iron source, phosphate source, carbon source and rare earth metal source is 2:1:2:1:0.01-0.05, the amount of deionized water is 20-50 mL, the heating temperature is 60-100° C., the heating time is 3 h-6 h, and the stirring time is 4 h-8 h.
8. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 4, characterized in that: In step 2, vacuum drying is performed at 100-150° C. for 10-12 hours.
9. The method for preparing a modified sodium iron pyrophosphate positive electrode material according to claim 5, characterized in that: In step 3, the sintering temperature is 500-800°C, the heating rate is 3-5°C / min, the sintering time is 10-12h, and the protective gas during sintering is argon.
10. An application of a modified sodium iron pyrophosphate positive electrode material, characterized in that: The modified sodium iron pyrophosphate positive electrode material described in claim 1 is applied to a sodium ion battery.
Citation Information
Patent Citations
Na3.64Fe2.18(P2O7)2 positive electrode material, and preparation method and application thereof
CN106629648A
Composite electrode material of sodium cobalt pyrophosphate / carbon, preparation and application of composite electrode material
CN107017393A
Carbon-coated pyrophosphoric acid polyanion composite material as well as preparation method and application thereof
CN116190640A
Iron-based polyphosphate material with uniform mesoporous structure as well as preparation and application of iron-based polyphosphate material
CN118561258A
Cathode Active Material for Secondary Battery
KR1020140000490A
Cited By
Preparation method of sodium-ion battery positive electrode material and product and application of sodium-ion battery positive electrode material
CN121748374A